2009
DOI: 10.1088/0004-637x/702/2/1268
|View full text |Cite
|
Sign up to set email alerts
|

Faint Fuzzy Star Clusters in NGC 1023 as Remnants of Merged Star Cluster Complexes

Abstract: In the lenticular galaxy NGC 1023 a third population of globular clusters (GCs), called faint fuzzies (FFs), was discovered next to the blue and red GC populations by Larsen & Brodie. While these FFs have colors comparable to the red population, the new population is fainter, larger (R eff > 7 pc) and, most importantly, shows clear signs of co-rotation with the galactic disk of NGC 1023. We present N-body simulations verifying the hypothesis that these disk-associated FFs are related to the young massive clust… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 28 publications
2
34
0
Order By: Relevance
“…Kroupa 1998;Fellhauer & Kroupa 2002aBekki et al 2004;Brüns et al 2009. These studies demonstrated that the merging star cluster scenario provides a mechanism for the formation of EOs.…”
Section: An Eo Formation Scenariomentioning
confidence: 71%
See 1 more Smart Citation
“…Kroupa 1998;Fellhauer & Kroupa 2002aBekki et al 2004;Brüns et al 2009. These studies demonstrated that the merging star cluster scenario provides a mechanism for the formation of EOs.…”
Section: An Eo Formation Scenariomentioning
confidence: 71%
“…In addition, Brüns et al (2009) discussed the origin of the EOs, or faint fuzzies, associated with the disk of NGC 1023 in the context of merged cluster scenario and demonstrated that the observed structural parameters of the faint fuzzies are in excellent agreement with the modeled merger objects.…”
Section: An Eo Formation Scenariomentioning
confidence: 90%
“…Burkert et al (2005) analyzed the kinematics of the faint fuzzies and concluded that they form a ring-like structure within the galactic disk of NGC 1023 and that this ring was probably formed during a galaxy-galaxy interaction comparable to the Cartwheel galaxy. A detailed discussion of faint fuzzies in the context of merged CCs is given in Brüns et al (2009), who demonstrated that the observed structural parameters of the faint fuzzies are in excellent agreement with the merged CC scenario.…”
Section: Discussionmentioning
confidence: 89%
“…Recent mergers of star clusters in star cluster complexes can host a variety of substructures in the form of faint envelopes, tidal tails, and nonmerged companion GCs (e.g., Brüns et al 2011Brüns et al , 2009Fellhauer & Kroupa 2005). Whereas in some simulations of UCD-like objects the surrounding GC companions have merged into the central object within the first Gyr (Brüns et al 2011), and thus the merging process is finished.…”
Section: Spatial Correlation Of Gcs With Ucdsmentioning
confidence: 99%
“…An alternative explanation for the clustering of GCs around UCDs could be that those UCDs initially formed in a star cluster complex that then subsequently merged to create a UCD (see, e.g., Fellhauer & Kroupa 2002;Brüns et al 2009Brüns et al , 2011. Massive star cluster complexes are common in gas-rich mergers (e.g., The Antennae, Whitmore et al 1999).…”
Section: Spatial Correlation Of Ucds With Globular Clustersmentioning
confidence: 99%